Penguatan Etika Keilmuan dalam Pembelajaran Matematika untuk Mendorong Berpikir Reflektif Siswa : A Systematic Literature Review - Annisa, Selfiana; Suciptaningsih, Oktaviani Adhi; Anggraini, Ade Eka; Rufiana, Intan Sari; Mardhatillah, Mardhatillah; Mashfufah, Aynin; Arifin, Slamet (Media Pendidikan Matematika, 2025)
Mathematics learning not only serves as a means of mastering concepts and procedures, but also as a space for shaping scientific attitudes that are reflected in scientific ethics. This study aims to systematically examine the integration of scientific ethics in mathematics learning and its contribution to the development of students' reflective thinking skills. The study uses the PRISMA-based Systematic Literature Review (SLR) based on PRISMA by examining Scopus-indexed articles published between 2020 and 2025. Inclusion criteria included empirical and conceptual articles discussing mathematics learning, scientific ethics, and students' reflective thinking, while exclusion criteria included irrelevant articles, duplicates, and non-Scopus publications. From the selection process, 11 final articles were obtained and analyzed using descriptive-qualitative techniques based on indicators of scientific ethics, mathematics learning strategies for reflective thinking, and trends in the development of students' reflective thinking. The results of the study show that the integration of scientific ethical values such as academic honesty, careful reasoning, the ability to justify, and openness to various problem-solving strategies contributes significantly to improving the quality of students' cognitive reflection. Learning that emphasizes discussion, critical dialogue, and analysis of the thinking process has proven effective in internalizing scientific values. Theoretically, this study enriches the conceptual framework of mathematics learning by placing scientific ethics as the foundation for the development of reflective thinking, while also providing direction for the development of learning designs that are oriented towards process and academic values.